Ethnobotanical importance of brinjal in India - Tiwari, Shailesh K; Mishra, Pallavi; Rai, Krishna Kumar (Indian Horticulture, 2020)
Brinjal is an important vegetable crop which has been known for its culinary and therapeutic uses since ancient times. The cultivar differences concern mainly the peel colour, shape, size and weight of comestible fruits, but the chemical composition, earliness of fruiting, and environmental-posed challenges also play a significant role in genesis of variability and acquisition of different morphological forms. Variation in morphology and biochemical content in brinjal fruits is an important factor that governs the choice of fruit for human consumption or liking for a specific type. The genetic differences among the genotypes are potentially relevant to breeding programs in that the variability created through hybridization of the contrasting forms could be exploited. Although it is a popular vegetable in India, the various plant parts are also used as medicines for treatment of inflammations, cardiac disabilities, bronchitis, asthma and several forms of neuralgias.